DNA Profiling in Forensic Science: A Review - Jaya Lakshmi Bukyya; M L. Avinash Tejasvi; Anulekha Avinash; Chanchala H. P.; Priyanka Talwade; Mohammed Malik Afroz; Archana Pokala; Praveen Kumar Neela; T K. Shyamilee; Vammi Srisha (Global Medical Genetics, 2021)
DNA is present in most of the cells in our body, which is unique in each and every individual, and we leave a trail of it everywhere we go. This has become an advantage for forensic investigators who use DNA to draw conclusion in identification of victim and accused in crime scenes. This review described the use of genetic markers in forensic investigation and their limitations.